Estimation of daily fluoride intake of infants using the microdiffusion method - Ryosuke Yanagida; Ryouichi Satou; Naoki Sugihara (Elsevier, 2019)
Background/purpose: The standard of daily fluoride intake (DFI) has been discussed mainly for adults since 1950s in Japan. Although dietary habits have changed significantly in recent years, there have been no further studies on DFI in the past 10 years, and the need for further review has been discussed. Additionally, fluoride bioavailability in infants is higher than that in adults; hence, an excess fluoride intake often manifests symptoms. However, the number of studies on the DFI of infants is less than that of adults. The purpose of this study is to investigate the DFI for Japanese infants to provide adequate fluoride application. Materials and methods: 20 products of infant foods for 4 age groups, 5 products of infant formulas, and 5 products of bottle water available in retail stores in Japan were prepared for this study. Fluoride concentration of each product was measured by microdiffusion method and fluoride ion-selective electrode, and then DFI in infants aged 5, 7, 9, and 12 months were calculated. Results: According to our study, the DFI in infants aged 5, 7, 9, and 12 months is 185.34 μg/day, 181.16 μg/day, 174.59 μg/day, and 179.19 μg/day, respectively. Conclusion: From this result, it is estimated that the DFI from infant food and beverages in Japan is lower than the standard in other countries. Lifestyles and dietary habits are different in each country, and a new standard of DFI for Japanese children is required to meet the adequate fluoride recommendation. Keywords: Drinking water, Fluorides, Infant food, Infant formula, Preventive dentistry